2013
DOI: 10.1021/la401527j
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Particles from Emulsion Polymerization of Methyl Methacrylate in the Presence of Quaternary Ammonium Surfactants

Abstract: The purpose of this Article is to characterize polymeric particles of poly(methylmethacrylate) (PMMA) synthesized in the presence of one of two different quaternary ammonium surfactants (QACs): cetyltrimethylammonium bromide (CTAB) or dioctadecyldimethylammonium bromide (DODAB). The methods used are dynamic light scattering for sizing, polydispersity and zeta potential analysis, scanning electron microscopy (SEM) for morphology visualization, and plating plus colony-forming unities (CFU) counting for the deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 29 publications
0
73
0
Order By: Relevance
“…They observed the antimicrobial effect dependent on the amount of positive charge on particles and independent of particle sizes [178]. In a more recent investigation, they characterized antimicrobial polymer particles of poly(-methylmethacrylate), which were prepared by emulsion polymerization in the presence of quaternary ammonium surfactants [179]. It was found that high surfactant concentrations yielded stable colloids with permanent cationic groups that were significantly antibacterial.…”
Section: Antimicrobial Polymer Assembliesmentioning
confidence: 99%
“…They observed the antimicrobial effect dependent on the amount of positive charge on particles and independent of particle sizes [178]. In a more recent investigation, they characterized antimicrobial polymer particles of poly(-methylmethacrylate), which were prepared by emulsion polymerization in the presence of quaternary ammonium surfactants [179]. It was found that high surfactant concentrations yielded stable colloids with permanent cationic groups that were significantly antibacterial.…”
Section: Antimicrobial Polymer Assembliesmentioning
confidence: 99%
“…The cationic lipid dioctadecyldimethylammonium bromide (DODAB), the antimicrobial peptide gramicidin D (Gr), the antimicrobial cationic polymer poly (diallyldimethylammonium chloride) (PDDA) and the biocompatible polymer poly (methyl methacrylate) (PMMA) can be combined to yield a variety of antimicrobial cationic nanostructures as previously described by our group (Carmona Ribeiro and Chaimovich, 1983; Martins et al, 1997; Lincopan et al, 2003, 2005; Pereira et al, 2008; Melo et al, 2010, 2011; Carvalho et al, 2012; Naves et al, 2013; Ragioto et al, 2014; Carrasco et al, 2015; Sanches et al, 2015). However, these nanostructures were not specifically evaluated against foodborne pathogens before.…”
mentioning
confidence: 99%
“…PMMA/DODAB and PMMA/PDDA NPs were obtained as previously described (Naves et al, 2013; Sanches et al, 2015). …”
mentioning
confidence: 99%
“…The hydrogel particles are colloidally stable and responsive to various biologically relevant stimuli, such as temperature, pH, and oxidation. For example, their feature of positive charge could be utilized for antimicrobial treatment, 17,18 or to support cell delivery 19,20 in tissue engineering and regenerative medicine. For example, many potentially therapeutic biomolecules are anionic, such as nucleic acids (DNA, silencing RNA, single-stranded oligonucleotide) and proteins.…”
Section: Introductionmentioning
confidence: 99%